Acute kidney injury in acute liver failure: a review. (November 2013) - Moore, Joanna K; Love, Eleanor; Craig, Darren G; Hayes, Peter C; Simpson, Kenneth J
Acute liver failure is a rare and often devastating condition consequent on massive liver cell necrosis that frequently affects young, previously healthy individuals resulting in altered cognitive function, coagulopathy and peripheral vasodilation. These patients frequently develop concurrent acute kidney injury (AKI). This abrupt and sustained decline in renal function, through a number of pathogenic mechanisms such as renal hypoperfusion, direct drug-induced nephrotoxicity or sepsis/systemic inflammatory response contributes to increased morbidity and is strongly associated with a worse prognosis. Improved understanding of the pathophysiology AKI in the context of acute liver failure may be beneficial in a number of areas; the development of new and sensitive biomarkers of renal dysfunction, refining prognosis and organ allocation, and ultimately leading to the development of novel treatment strategies, these issues are discussed in more detail in this expert review.